2022
DOI: 10.3390/toxics10050250
|View full text |Cite
|
Sign up to set email alerts
|

CeO2-Zn Nanocomposite Induced Superoxide, Autophagy and a Non-Apoptotic Mode of Cell Death in Human Umbilical-Vein-Derived Endothelial (HUVE) Cells

Abstract: In this study, a nanocomposite of cerium oxide-zinc (CeO2-Zn; 26 ± 11 nm) based on the antioxidant rare-earth cerium oxide (CeO2) nanoparticles (NPs) with the modifier zinc (Zn) was synthesized by sintering method and characterized. Its bio-response was examined in human umbilical-vein-derived endothelial (HUVE) cells to get insight into the components of vascular system. While NPs of CeO2 did not significantly alter cell viability up to a concentration of 200 µg/mL for a 24 h exposure, 154 ± 6 µg/mL of nanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“… 17 Although BiCl 3 showed a high biofilm eradication, it showed low cell viability of host cells, which may be due to bismuth-induced oxidative stress, mitochondrial dysfunction, and consequently, apoptosis-like mode of cell death in human cells. 18 According to our study, it was found that mouthwash containing BiCl 3 showed high toxicity to both oral and gastric cells. While the mouthwash containing poly l -Lysine and glycerol monolaurate has low cytotoxicity to human periodontal ligament cells (PDL cells), human oral keratinocyte cells (H357 cells), and human gastric adenocarcinoma cells (AGS cells), glycerol monolaurate showed no cytotoxicity to dendritic cells and human gingival fibroblast cells according to a previous study.…”
Section: Discussionmentioning
confidence: 75%
“… 17 Although BiCl 3 showed a high biofilm eradication, it showed low cell viability of host cells, which may be due to bismuth-induced oxidative stress, mitochondrial dysfunction, and consequently, apoptosis-like mode of cell death in human cells. 18 According to our study, it was found that mouthwash containing BiCl 3 showed high toxicity to both oral and gastric cells. While the mouthwash containing poly l -Lysine and glycerol monolaurate has low cytotoxicity to human periodontal ligament cells (PDL cells), human oral keratinocyte cells (H357 cells), and human gastric adenocarcinoma cells (AGS cells), glycerol monolaurate showed no cytotoxicity to dendritic cells and human gingival fibroblast cells according to a previous study.…”
Section: Discussionmentioning
confidence: 75%
“…•− levels in control and BNP-treated HUVE cells by applying direct and indirect methods of investigation, followed by other relevant markers of oxidative stress such as lipid peroxidation and mitochondrial function, as shown in some recent publications [13][14][15]. LPO was assessed using live cell imaging by applying BODIPY dye, and using the biochemical method of quantifying thiobarbituric acid reactive substances (TBARS).…”
Section: Introductionmentioning
confidence: 99%